Intelligent control rod selection algorithm for core power control at TRIGA Puspati Reactor using fuzzy logic technique - Che Soh, Azura; Abdul Rahman, Ribhan Zafira; Minhat, Mohd Sabri; Gunasegaran, S. (UTEM, 2025)
The TRIGA PUSPATI Reactor (RTP) serves as Malaysia's primary research reactor, supporting a range of nuclear applications. A critical element in its operation is the control rod selection algorithm (CRSA), which regulates reactor power and ensures stability. The conventional CRSA (cCRSA), however, faces challenges in managing transient operations and achieving precise steady-state control due to fluctuations in control rod worth. To address these issues, a new fuzzy logic-based control rod selection algorithm (Fuzzy-CRSA) has been developed and validated through MATLAB simulations. This Fuzzy-CRSA approach provides a more flexible and resilient method for controlling the reactor’s four types of rods. By optimizing rod selection and movement, Fuzzy-CRSA achieves faster response times and greater stability compared to the cCRSA, with improvements in rise time from 0.57% to 27.67% and in settling time from 3.14% to 25.88%. These results highlight Fuzzy-CRSA’s capability to more effectively meet the RTP’s power requirements, enhancing reactor performance and supporting Malaysia’s nuclear research progress.